Solve for \( x \) : (a) \( \quad x^{\frac{1}{2}}-3 x^{\frac{1}{4}}+2=0 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the equation \( x^{\frac{1}{2}} - 3x^{\frac{1}{4}} + 2 = 0 \), we can make a substitution to simplify it. Let \( y = x^{\frac{1}{4}} \). Then, we have \( y^2 = x^{\frac{1}{2}} \). Substituting into the equation gives us: \[ y^2 - 3y + 2 = 0. \] Now, we can factor this quadratic equation: \[ (y - 1)(y - 2) = 0. \] Setting each factor to zero gives us the solutions: 1. \( y - 1 = 0 \) ⟹ \( y = 1 \) 2. \( y - 2 = 0 \) ⟹ \( y = 2 \) Now we substitute back to find \( x \): 1. If \( y = 1 \), then \( x^{\frac{1}{4}} = 1 \) ⟹ \( x = 1^4 = 1 \). 2. If \( y = 2 \), then \( x^{\frac{1}{4}} = 2 \) ⟹ \( x = 2^4 = 16 \). Thus, the solutions for \( x \) are: \[ \boxed{1} \quad \text{and} \quad \boxed{16}. \]